ISOLATION AND INHIBITION TEST OF QUERCETIN COMPOUND FROM OKRA FRUIT (Abelmoschus esculentus L.) - Christina Astutiningsih (Universitas Muhammadiyah Magelang, 2021)
Okra (Abelmoschus esculentus L.) is one of the plants from the Malvacea. The secondary metabolite compounds with quite large composition flavonoid compound that is able to provide pharmacological activity to lower blood sugar. This study aimed to isolate, identify find out the results of the inhibition test on the alpha amylase enzyme one of enzyme that affects blood sugar levels. Herein, the extraction was initially carried out using the remaceration method of okra fruit powder using 80% ethanol followed by fractionation process using n-hexane, ether, and ethyl acetate. The marker was isolated using the preparative TLC method with a silica gel and n-butanol:acetic acid : water (4:1:5) as stationary and mobile phases. The isolates were a yellow powder with a yield of 0.18% and a melting point of 307-309.5oC. TLC Densitometry was used to determine the Rf value and the spectral form of the standard quercetin and isolates wich are found to be identical. The isolate showed that quercetin compounds had the inhibitory power of the amylase enzyme by 49.74% compared to acarbose 58.90%. IC values, by quercetin isolates were8,358/ml and acarbose 7,598mg/ml and statistically, the t-group showed no significant differences.